Global, regional, and country‐level estimates of hepatitis C infection among people who have recently injected drugs. (28th August 2018) - Grebely, Jason; Larney, Sarah; Peacock, Amy; Colledge, Samantha; Leung, Janni; Hickman, Matthew; Vickerman, Peter; Blach, Sarah; Cunningham, Evan B.; Dumchev, Kostyantyn; Lynskey, Michael; Stone, Jack; et al.
Abstract: Background and Aims: People who have recently injected drugs are a priority population in efforts to achieve hepatitis C virus (HCV) elimination. This study estimated the prevalence and number of people with recent injecting drug use living with HCV, and the proportion of people with recent injecting drug use among all people living with HCV infection at global, regional and country‐levels. Methods: Data from a global systematic review of injecting drug use and HCV antibody prevalence among people with recent (previous year) injecting drug use were used to estimate the prevalence and number of people with recent injecting drug use living with HCV. These data were combined with a systematic review of global HCV prevalence to estimate the proportion of people with recent injecting drug use among all people living with HCV. Results: There are an estimated 6.1 million [95% uncertainty interval (UI) = 3.4–9.2] people with recent injecting drug use aged 15–64 years living with HCV globally (39.2% viraemic prevalence; UI = 31.6–47.0), with the greatest numbers in East and Southeast Asia (1.5 million, UI = 1.0–2.1), eastern Europe (1.5 million, UI = 0.7–2.4) and North America (1.0 million, UI = 0.4–1.7). People with recent injecting drug use comprise an estimated 8.5% (UI = 4.6–13.1) of all HCV infections globally, with the greatest proportions in North America (30.5%, UI = 11.7–56.7), Latin America (22.0%, UI = 15.3–30.4) and eastern Europe (17.9%, UI = 8.2–30.9). Conclusions: Although, globally, 39.2% of people with recent injecting drug use are living with hepatitis C virus (HCV) and 8.5% of all HCV infections occur globally among people with recent injecting drug use, there is wide variation among countries and regions.